MOBILITAS SOSIAL EKONOMI MIGRAN DARI DESA BANTAN AIR KE MALAYSIA - Tri Susila Nasution; T. Romy Marnelly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Background of this research comes to observation about situation that therechanges social economy in society especially in Bantan Air who became migranto Malay. Formulation in this research are what is the factor that makes themigran interest to go to Malay and how their social economy from village toMalay. The goal of this research is to see the factors that make the migran interestto go to Malay.This research was done in Bantan Air at August 2014. Informan who be thesubject is society in Bantan Air that worked in Malay. All of the data wascollected through observation, interview, and documentation technics. Beside thatdata analysis technic was done to looking for research result from researchlocation it means descriptive qualitative technic.Result in this research showed that there are change from social andeconomy side of the migran who worked in Malay. The change can be seen fromtheir increase income, home style looking good, also they had many aset. It meansthat they had climbing social mobility, but not all of migran have the same thing.Some of them stay away in same position like before they became migran, inother word, they don’t have change. This situation shows they have sinkingmobility.Keywords : Social, Economy, Mobility and Migran.